The construction of Latin American cultural identity in Manuel Ugarte’s correspondence - Fatima, KHELIFA (Journal of Ecohumanism, 2026)
This research paper analyses the political and intellectual stance of Manuel Ugarte, an Argentine writer, journalist and diplomat, noted for his steadfast defence of the Latin American cause. The writer maintained an extensive correspondence with intellectuals of international standing to highlight a shared concern centred on the search for a distinct continental voice, whilst rejecting all forms of political, economic and cultural subordination to the United States. These men of letters defended their own identity, rooted in indigenous culture, mestizo heritage and local traditions, whilst not entirely distancing themselves from European and North American influences. Much of the correspondence demonstrates that this intellectual community drew primarily on the historical context of the era and the circumstances surrounding it. From this perspective, the study of this correspondence aims to highlight the political, cultural and ideological aspirations that Latin American intellectuals sought to convey, employing a historical-intellectual approach, as well as analysing the discursive strategies used in the construction of Latin American identity.